Framtagning av vinschanordning till drönare för leverans ut till havs - Larsson, Sara; Gundersen, Adam (My University, 2021)
Commissioned by Swedish Sea Rescue Society, a winch device for a drone has been developed to enable transportation of rescue related supplies at sea. When an incoming alarm occurs, the drone will be loaded with a specific payload and then take-off to the desired destination. When the drone has reached the location, it will circulate around the delivery spot, for example a boat, while hoisting down the payload. The payload will release itself when the ground level is reached, or a person catches it and unloads it manually. When the payload is released, the drone will winch the line up again and the delivery stage is completed. The drone can now either keep monitoring the situation or return to shore again. Since this project by Swedish Sea Rescue Society to develop a complete winch device for a drone is in a very early stage where no previous work is made in the subject yet, very few boundaries were pre-established. To clarify these boundaries and determine what is and what is not included in this thesis, a process schedule all the way from the start to the end of the delivery stage was made. With the help of this scheme, a decision was made to divide the problem into two different sub-problems, one for the concept development of the winch mechanism and one for the fastening mechanism. This facilitates the structure and time allocation of the work. The main focus in this project was to create best basis possible for the future work in the area. This is done by forming many different concepts for both the fastening- and winch mechanism. The concept development stage began with the fastening mechanism since it after some discussion became clear that it is easier to adapt the winch mechanism to the fastening mechanism than the other way around. Different partial solutions generated several concepts for the fastening mechanism where elimination matrices produced a few resulting concepts. The remaining resulting concepts were developed along with simple prototypes to make a better understanding of the different concept’s functions, strengths and weaknesses and also to create a better basis for making a good decision for which concept to continue develop. This decision for the final concept of the fastening mechanism however was put on hold until the final concept for the winch mechanism was determined. One of the selection parameters that affected the decision-making process of the final concepts was the possibility to test the solutions on a prototype model in order to verify its functions. Therefor a purchase of electric components such as an electric motor and sensors for the winch was made, to power the winch and detect the force in the wire so that the verification could be made. A detailed and accurate development along with protype manufacturing were made on both of the final concepts to establish the result presented in this report. The result of the final concepts was presented with distinct pictures of the 3D-models and the prototypes made by additive manufacturing, both for the winch and fastening mechanism apart and combined together. Discussions about the result, detection through the project and further recommendations ended this work and opens for development with a wide base of knowledge.